HIV and the gut: implications for HIV persistence, immune dysfunction and cure strategies - Lau, Jillian S. Y.; Lewin, Sharon R.; Telwatte, Sushama (Frontiers in immunology, 2025)
The intestinal immune compartment plays a central role in HIV pathogenesis, serving as an early site for viral replication and a significant reservoir for latent infection. Despite the success of antiretroviral therapy (ART) in suppressing plasma viremia, HIV persists indefinitely in latently infected cells, commonly found in the intestinal tract due to its unique immunological and structural environment. Targeting HIV-infected cells that persist in the intestinal tract is an important consideration for therapeutic strategies and is also important when considering an HIV cure. This review describes the therapeutic approaches aimed at addressing HIV persistence in the intestinal tract, or gut. We provide a brief overview of mechanisms underlying reservoir formation and maintenance, discuss the challenges posed by gut-specific factors, and examine emerging strategies, including latency reversal agents, immune modulation, gut-targeted ART, and novel delivery systems. This review will focus on contemporary advances in knowledge in this space, gaps in the literature and areas for future research focus.